Produksi Film Pendek âLike And Dislike â Menggunakan Sistem Multimedia - Utomo, Pandu; Purnama, Bambang Eka; Urbani, Yunan Hepy (Fakultas Teknologi Informatika Universitas Surakarta, 2014)
Abstract - Development of the University of Surakarta assessed memorable film monotonous, it does not result in the development of cinema that puts the educational aspect. Short Film Production